The Objectives Which We Suggest for Quebec

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
DOMTAR has invested in Quebec a large part of its capital, maintains over 7,000 employees (40% of its Canadian work force) in that province and has located its head office in Montreal. Its markets, however, are international. Thus its basic interest on constitutional, cultural, and linguistic matters.